Student satisfaction with hospitality program components in selected universities in the National Capital Region - Lim, Mina Ramos
The study aimed to determine the extent to which students are satisfied with teaching, advising, curriculum and learning facility as components of hospitality programs. An institutional information sheet, a pre-tested questionnaire and a questioning route were used to collect data. Expectation, perceived performance, satisfaction, difference between "private" and "public" and reasons for satisfaction and dissatisfaction were analyzed using Expectation-Performance Analysis (EPA), performance gap, perceived performance, Mann-Whitney U and focus group discussions. Data from 169 respondents from two private and two public universities in Metro Manila showed all were single, and predominantly female (75%), between 19 and 20 years old. Most rated themselves from average to above average in their class standing. Six students in private and nine in public schools joined the focus group discussions. Expectation was higher than perceived performance level. Specifically, expectation scores were rated above 4 or "more than expected", while perceived performance scores were rated between 3 to 4 or "neutral" to "satisfied". Curriculum had the highest expectation among participants. Advising had the lowest rating in "private" while facility had the lowest in "public" schools. In general, expectation and corresponding perceived performance scores hugged closely together. Respondents rated teaching with the highest perceived performance while facility, the lowest. These ratings were the average of the results of the two types of schools. Students in "private" had the highest perception of performance in facility and the lowest in advising. Students in "public" had the highest performance rating in teaching and the lowest in facility. Expectation was plotted against perceived performance to identify strengths and challenges. Students in "private" had considered facility and curriculum as strengths, teaching as a challenge, and advising as low priority. Students in "public" had considered curriculum, advising, and teaching as strengths and facility as low priority. Although facility was a low priority in EPA, it had the largest performance gap or the lowest satisfaction level, and the lowest perception of performance. Facility was the greatest challenge in "public" institutions. Students in "private" depended on curriculum and facility for their satisfaction while students in "public" depended more on curriculum, teaching, and advising for their fulfillment. Seemingly, students make the most out of their situation. When one component is lacking, students tend to look for fulfillment in the other stronger components that fill up the limitation or gap. The rank order using performance gap of all participants was (1) advising, (2) teaching, (3) curriculum and (4) facility, wherein 1 indicated the smallest gap. In "private", the rank order was (1) advising, (2) teaching, (3) facility and (4) curriculum while in "public", it was (1) teaching, (2) advising, (3) curriculum and (4) facility. Using Mann-Whitney U for the difference test, the two types of schools were comparable in satisfaction level using performance gap in teaching, advising, and curriculum, except in facility. Students appreciated teachers who are knowledgeable and courteous, approachable advisers who inform and listen, a meaningful practicum, relevant subject matter, clear academic requirements, reasonable library hours and adequate library materials. On the other hand, teachers' promptness in giving feedback on students' progress and advisers' understanding of their students' potentials were cited as areas that need to be improved. Moreover, students wanted their institutions to offer major subjects when they needed and more adequate and well-equipped laboratories. The FGDs revealed that students enjoyed the opportunities and exposures that the school provided. Teachers' competency and warmth, advisers' availability and "motherly" approach, experiental learning, and adequacy of facilities provided satisfaction, while unfair grading, teachers' dysfunctions, adviser's time constraints, inadequate facilities such as slow internet connection and inaccessible printing services (Pri-2), and poor condition of kitchen tools and equipment (Pub-2) were sources of dissatisfaction among students. This study recommended improvements in all hospitality components most especially in the learning facility of public institutions and the use of combination of EPA, performance gap and perceived performance in analyzing satisfaction level. Further studies may be conducted to validate the results of the study, to strengthen evaluation tools, and to understand satisfaction better in relation to students' learning and development.